2011
DOI: 10.5194/npg-18-635-2011
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization and desynchronization in the Olami-Feder-Christensen earthquake model and potential implications for real seismicity

Abstract: Abstract. The Olami-Feder-Christensen model is probably the most studied model in the context of self-organized criticality and reproduces several statistical properties of real earthquakes. We investigate and explain synchronization and desynchronization of earthquakes in this model in the nonconservative regime and its relevance for the power-law distribution of the event sizes (Gutenberg-Richter law) and for temporal clustering of earthquakes. The power-law distribution emerges from synchronization, and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…These asperity events form spatio-temporal clusters with pronounced characteristic features. The processes of synchronization and desynchronization in the OFC model with short-term correlations among events were also observed [38]. It was suggested that synchronization in the model drives it into a state with scale-invariant power-law distributed events while desynchronization results in the occurrence of aftershocks and foreshocks.…”
Section: The Olami-feder-christensen (Ofc) Modelmentioning
confidence: 83%
“…These asperity events form spatio-temporal clusters with pronounced characteristic features. The processes of synchronization and desynchronization in the OFC model with short-term correlations among events were also observed [38]. It was suggested that synchronization in the model drives it into a state with scale-invariant power-law distributed events while desynchronization results in the occurrence of aftershocks and foreshocks.…”
Section: The Olami-feder-christensen (Ofc) Modelmentioning
confidence: 83%
“…Hence, b ≈ 1 means that the exponent γ is around γ = 1.6-1.7. The above are some of the reasons why the OFC model is considered to be the prime example [106] for a supposedly SOC system for earthquakes, but the question of whether real earthquakes are described or not by SOC models of this type, or whether other kinds of mechanisms, e.g., [107][108][109], need to be involved, still remains unsolved [82,86,100,[110][111][112][113][114].…”
Section: Olami-feder-christensen Earthquake Modelmentioning
confidence: 99%
“…The model is an extended version of the OFC model, which itself is a kind of paradigm for SOC in non-conserved systems (Hergarten and Krenn, 2011), but it works differently from the original OFC model as a finite value of the driving rate ν is applied. By increasing the values of ν, which quantifies the rate of approaching instability, the system undergoes a smooth transition from a correlated regime characterized by power laws to an uncorrelated regime in frequency-size statistics (Piegari et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%